Managing E-Waste Using the Symbiosis Perspective - Emy Ezura A Jalil (International Journal of Supply Chain Management, 2017)
The production of electrical and electronic equipment (EEE) specifically mobile devices is one of the fastest growing global manufacturing activities. This development has resulted in an increase of waste electric and electronic equipment (WEEE). Rapid economic growth, coupled with urbanization and growing demand for consumer goods, has increased both the consumption of EEE and the production of WEEE, which can be a source of hazardous wastes that pose a risk to the environment and to sustainable economic growth. WEEE includes discarded electronic and electrical equipment. Managing WEEE typically is complex and requires a structured disposal method. However, the process of disposal WEEE sustainably started with a proper sorting and separating from the source, therefore the consumers are under assumption should be aware of the WEEE disposal method. The paper has found consumers are required to have higher awareness level and this awareness level is influenced by two situational factors which are engagement process and supporting facilities and consumers knowledge on the WEEE itself. Both situational and personal factors are concomitantly necessary to improve the recapturing of WEEE back into the supply chain. This phenomenon is considered symbiotic whereby both factors are equally important in order to acquire sustainability in improving the backwards movement in the logistics.